Experimentally induced volumetric re-equilibration of plagioclase-hosted melt inclusions - Drignon, Mélissa J. (2021)
The application of melt inclusions (MI) to infer magmatic processes assumes the MI have remained as constant mass, constant volume systems since the time of trapping. Understanding the effects of both compositional and volumetric re-equilibration is key for the interpretation of MI data. Although the re-equilibration behavior MI in quartz and olivine has been studied in some detail, the process is less understood for other MI host phases such as plagioclase, a common phase in igneous rocks. A MI can re-equilibrate when it experiences pressure and temperature (PT) conditions that differ from formation PT conditions. During laboratory heating, irreversible MI expansion may occur. As a result, the internal pressure within the MI decreases, resulting in chemical and structural changes to the MI and host. We present results of heating experiments on plagioclase-hosted MI designed to induce volumetric re-equilibration. The experiments consisted of incrementally heating the MI to temperatures above the homogenization temperatures. At ∼40°C above, the temperature at which the daughter minerals melted, irreversible volume expansion lowered the pressure in the MI, and led to exsolution of CO2 into vapor bubbles. With each additional few degrees of heating, additional episodes of CO2 exsolution, bubble nucleation and expansion of the vapor bubbles occurred. Re-equilibration of MI in plagioclase occurred through a combination of ductile and brittle deformation of the host surrounding the MI, whereas previous studies have shown that MI in olivine re-equilibrate dominantly through ductile deformation associated with movement along dislocations. This behavior is consistent with the differing rheological properties of these phases.